Formulation Optimization Of Bilayer Floating Tablet Of Famotidine - DR. S. D. BARHATE,; YOGESH RUPNAR,; RAHUL RAHANE,; DR. M. M. PATEL, (International Journal of Pharma and Bio Sciences, 2010)
The gastroretentive drug delivery system can be retained in the stomach and assist in improving the oral delivery of drugs with this objectives bilayer floating tablets of famotidine were prepared by using HPMC K100LV, HPMC K4MCR, sodium bicarbonate, sodium alginate, sodium starch glycolate, croscarmellose, crospovidone and lactose. Box-Behnken factorial design was used to statistically optimize the controlled release layer composition and evaluation of the effect of amount of HPMC K100LV (X1), amount of HPMC K4MCR (X2) and amount of sodium bicarbonate (X3) on release rate of famotidine. The polymers HPMC K100LV, HPMC K4MCR showed better control over drug release. The formulated formulations of Box-Behnken factorial design showed zero-order drug release. The prognostic ability of Response Surface Methodology involving multiple response optimizations was proved in designing and optimization of controlled release pharmaceutical formulations. Response surface prediction plots are useful to show the effect of interactions on the responses and desirability approach is a promising tool for optimization.